Using an integrated teaching approach to facilitate student achievement of the learning outcomes in a preclinical medical curriculum in India - Vashe, Asha; Devi, Vasudha; Rao, Raghavendra; Abraham, Reem Rachel; Pallath, Vinod; Umakanth, Shashikiran (American Physiological Society, 2019)
Today most education institutions around the world have adopted the philosophy of outcome-based education. The emphasis in outcome-based education is achievement of outcomes; hence the curriculum should be designed in a way that it includes the components targeted specifically at achieving these outcomes. A discipline-based approach results in fragmentation of learning and lack of clinical applicability. Integrated teaching could be a solution to achieve required outcomes in a holistic way. Hence, the aim of this study was to develop, implement, and evaluate an integrated teaching module. Temporal coordination of the basic sciences, along with correlation of learned topics to clinical settings, was done in the first year of the undergraduate medical program. The module was evaluated by obtaining qualitative and quantitative feedback from students. Student assessment was conducted with a test that had case vignettes and multiple-choice questions. In addition, students' change in learning approaches and self-directed learning readiness were collected. Students' perception regarding the educational environment was also obtained. Analysis of the data showed positive feedback from the students regarding the integrated teaching. Students' average score in the test was 86%. There was a significant increase in the scores for the deep approach and self-directed learning readiness in the posttest compared with the pretest. Moreover, students were found to be satisfied with the educational environment. Evaluation of integrated teaching revealed that it was well accepted by the students. Moreover, it facilitated the achievement of the students' outcomes.